Sogoshosha : engines of export-based growth - Tsurumi, Yoshi, 1935- (Institute for Research on Public Policy, 1980)
From the back cover: Most Canadians have never heard of sogoshosha let alone know of their activities. And yet, it has been proposed that these Japanese general trading organizations may be developing into a prototype structure which will characterize much of international business in the future. In this study, Yoshi Tsurumi analyses the past and present development of these "large general trading firms" and their adaptation to dynamic changes in the business environment. The implications of Canada's increasing economic dependence on the United States and similarities between Canada and developing countries that have successfully created sogoshosha led the author to present a case for Canadian sogoshosha.